Prevalence of oral lesions and its associated risk factors among PLHIV availing anti-retroviral therapy from a selected tertiary care hospital, Puducherry - A cross sectional analytical study - Pradip Kumar Jana; Swaroop Kumar Sahu; K Sivaranjini; Abdoul Hamide; Gautam Roy (Wolters Kluwer Medknow Publications, 2022)
Background and Objectives: Oral lesions are among the earliest and most important indicators of infection with human immunodeficiency virus (HIV). The presence of oral lesions has a significant impact on the physical and mental health of the PLHIV. Hence, a novel attempt is made to assess the prevalence of various types of oral lesions among the adult people living with human immunodeficiency virus (PLHIV) undergoing antiretroviral therapy. Methodology: In this facility-based cross-sectional study, a total of 239 out of 300 eligible PLHIV were assessed between September and October 2018. All consecutive eligible patients encountered during the data collection period were included. Oral examination was carried out using disposable mouth mirrors, sterile piece of cotton, and bright illuminated torch. Results: The prevalence of oral mucosal abnormalities was found to be 25% (95% confidence interval: 20.03-30.97). The most prevalent oral lesions were acute necrotizing ulcerative gingivitis, acute necrotizing ulcerative periodontitis, and candidiasis. CD4 count <200 cells/mm3, current tobacco use, and alcohol usage were significantly associated with the prevalence of oral lesions. Conclusion and Recommendations: The study revealed that one-fourth of the study participants had oral lesions. Strategies for early detection and prompt treatment of oral lesions need to be planned and incorporated in the program to reduce the morbidity due to oral lesions.